The antagonistic activity of marine actinomycetes from mangrove ecosystem against phytopathogenic fungi Colletotrichum sp. KA - Qonita Gina Fadhilah; Iman Santoso; Yasman YASMAN (Society for Indonesian Biodiversity, 2021)
Abstract. Fadhilah QG, Santoso I, Yasman. 2021. The antagonistic activity of marine actinomycetes from mangrove ecosystem against phytopathogenic fungi Colletotrichum sp. KA. Biodiversitas 22: 642-649.  Marine actinomycetes from mangrove ecosystems are known to be potential antifungal-producing isolates against phytopathogenic fungi. The aim of this research was to obtain potential marine actinomycetes isolates against the phytopathogenic fungi Colletotrichum sp. KA. Screening of 15 marine actinomycetes isolates using a dual culture method with a plug technique showed that 80% of isolates have antagonistic activity, represented as a percentage of growth inhibition range from 47.96% to 84.94%. Among 12 potential isolates, six isolates (SM4, SM11, SM14, SM15, SM18, and SM20) were evaluated for delayed antagonistic activity with incubation periods of 6, 9, and 12 days using the plug and streak techniques. The results showed that the percentage of growth inhibition of selected isolates inclined to increase along with the incubation period prior to inoculation of Colletotrichum sp. KA. Delayed antagonist assays using the streak technique resulted in higher inhibition results compared to the plug technique. Furthermore, the non-delayed assays of the two selected isolates, SM11 and SM15, also inhibited Colletotrichum sp. KA 57.99% and 59.88%, respectively. The delayed antagonist assay with a shorter incubation period of the two selected isolates also showed an increased percentage of growth inhibition of Colletotrichum sp. KA. According to our research, the delayed antagonistic assay of marine actinomycetes isolates with a 12-day incubation period using a plug technique was representative to evaluate the percentage of growth inhibition.